Analysis of Improving the Quality of Services Using the Quality Function Deployment Method - Sufiarsah, Sevanya Rezkia; Aspiranti, Tasya (UNISBA Press, 2024)
Abstract. The primary objective of this research is to analyze and optimize the quality of service at Edulab Dago, which is one of the major high schools' tutoring centers, using the QFD method. This study aims at determining the most essential needs and requirements of customers and translating them into technical responses in order to enhance the quality of service. The structured approach followed by the research is: firstly, the distribution of questionnaires to Edulab students in grades 10, 11, and 12; secondly, analysis regarding which customer needs are the most critical will be obtained from the data collected; lastly, the QFD method associates the needs with technical responses, setting priorities on actions that Edulab should realize to improve service quality. Results show that the main customer concerns are the teaching staff's competence in guiding the students, the ability to explain the material clearly, and helpful physical modules and teaching materials. Technical responses in terms of regular quality control, training educators, and sufficient availability of teaching space have been recognized as paramount factors for the fulfillment of customer needs. This study concludes that if Edulab concentrates its efforts on these prioritized attributes and technical responses, the quality of its services will be significantly enhanced, increasing customer satisfaction and creating a stronger competitive position. It is envisaged that the findings and recommendations from this research will provide the strategic roadmap for Edulab to continually improve its services to meet the changing needs of students. Abstrak. Tujuan utama penelitian ini adalah untuk menganalisis dan mengoptimalkan kualitas layanan di Edulab Dago, yang merupakan salah satu pusat bimbingan untuk sekolah menengah, dengan menggunakan metode Quality Function Deployment (QFD). Penelitian ini bertujuan untuk menentukan kebutuhan dan persyaratan pelanggan yang paling penting serta menerjemahkannya menjadi tanggapan teknis untuk meningkatkan kualitas layanan. Pendekatan terstruktur yang diikuti dalam penelitian ini adalah sebagai berikut: pertama, distribusi kuesioner kepada siswa Edulab di kelas 10, 11, dan 12; kedua, analisis untuk mengetahui kebutuhan pelanggan yang paling kritis berdasarkan data yang dikumpulkan; dan terakhir, metode QFD menghubungkan kebutuhan dengan tanggapan teknis, menetapkan prioritas tindakan yang harus dilakukan oleh Edulab untuk meningkatkan kualitas layanan. Hasil penelitian menunjukkan bahwa perhatian utama pelanggan adalah kompetensi staf pengajar dalam membimbing siswa, kemampuan untuk menjelaskan materi dengan jelas, serta modul dan bahan ajar yang bermanfaat. Tanggapan teknis dalam bentuk kontrol kualitas rutin, pelatihan pendidik, dan ketersediaan ruang belajar yang memadai telah diidentifikasi sebagai faktor penting untuk memenuhi kebutuhan pelanggan. Penelitian ini menyimpulkan bahwa jika Edulab memfokuskan upayanya pada atribut dan tanggapan teknis yang diprioritaskan ini, kualitas layanannya akan meningkat secara signifikan, meningkatkan kepuasan pelanggan dan menciptakan posisi kompetitif yang lebih kuat. Diharapkan temuan dan rekomendasi dari penelitian ini akan memberikan peta jalan strategis bagi Edulab untuk terus meningkatkan layanannya agar sesuai dengan kebutuhan siswa yang terus berkembang. Kata kunci: Edulab Dago, Kualitas Layanan, Quality Function Deployment